Spatial structure and interspecific cooperation: theory and an empirical test using the mycorrhizal mutualism. - Verbruggen, E; El Mouden, C; Jansa, J; Akkermans, G; Bücking, H; West, SA; Kiers, E (2012)
Explaining mutualistic cooperation between species remains a major challenge for evolutionary biology. Why cooperate if defection potentially reaps greater benefits? It is commonly assumed that spatial structure (limited dispersal) aligns the interests of mutualistic partners. But does spatial structure consistently promote cooperation? Here, we formally model the role of spatial structure in maintaining mutualism. We show theoretically that spatial structure can actually disfavor cooperation by limiting the suite of potential partners. The effect of spatial structuring depends on the scale (fine or coarse level) at which hosts reward their partners. We then test our predictions by using molecular methods to track the abundance of competing, closely related, cooperative, and less cooperative arbuscular mycorrhizal (AM) fungal symbionts on host roots over multiple generations. We find that when spatial structure is reduced by mixing soil, the relative success of the more cooperative AM fungal species increases. This challenges previous suggestions that high spatial structuring is critical for stabilizing cooperation in the mycorrhizal mutualism. More generally, our results show, both theoretically and empirically, that contrary to expectations, spatial structuring can select against cooperation.